A Study on Affecting Factors of White-Nest Swiftlet (Collocalia fuciphaga) Farming Performance in Haurgeulis District, Indramayu Regency - Dodo Wahyudi; Suwarto Suwarto; Heru Irianto (Agriekonomika, 2019)
Indonesia is a major supplier of the white-nest products. The white-nest products can be originated from Java Island, including Haurgeulis District, Indramayu Regency. White-nest businesses in that area had been developed since 1950s although the productivity subsequently decline in the rate of deforestation of the concession area nowadays. These problems were henceforth set as the focus of the study, based on the inference Malcom Baldrige Criteria for Performance Excellence (MBCfPE). This study was to recognize the association white-nest business performance. Some internal factors, observed as the predictor factors of business performance, included achievement-motivation factor, strategic planning, technical aspects and technologies, guanxi (personal relationship), and leadership. Surveillance activities were undertaken by using simple random sampling with questionnaire method for collecting the primary data, processed by path analysis method. The test results shown that all of internal factor have significant effect on the performance of the white-nest business by the leadership intervening.